The role of light desynchronosis in regulating food behavior in Wistar rats in the experiment - E. G. Zarubina; I. A. Gribanov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Experimental modeling of light desynchronosis was performed on 60 male Wistar rats at the age of 6 months, weighing 280–300 g, to study its effect on food behavior. The experiment evaluated the amount of food consumed and the mass of animals. It was found that in conditions of round-the-clock lighting, there is a statistically significant increase in body weight and the amount of food consumed, compared with the control group.